Management of Alternaria spot in canola in function of sowing spaces and fungicides use (Revista de Ciências Agroveterinárias, 2023)
The Alternaria spot is one of the main canola’s diseases and it’s reported in all regions that producing this oleaginous, being transmitted by several ways. The aim of this study was to investigate whether sowing spacing in canola combined with the fungicides applications has an effect on the damage caused by Alternaria leaf spot and how these are reflected on crop yield. The studied hybrid was ‘Nuola 300’, and the experimental design used was randomized blocks with a subdivided plot scheme, with four replications. In the main plots, the row spacing (17 cm and 50 cm) was arranged, and in the subplots, the fungicides applications (T1 - control, without fungicide; T2 - azoxystrobin + tebuconazole, in stage B4; T3 - azoxystrobin + tebuconazole, in B4 and pyraclostrobin + fluxapyroxad, in B4 + 15 days; T4 - pyraclostrobin + fluxapyroxade, in stage B4 + 15 days). Under conditions in which the experiment was conducted, in the region of Erechim - Rio Grande do Sul, Brazil, there were control of Alternaria spot in canola leaves and siliques with the application of the fungicides azoxystrobin + tebuconazole and pyraclostrobin + fluxapyroxade, and the best control in siliques was obtained at 17 cm row spacing. The treatment with pyraclostrobin + fluxapyroxade in the 50 cm row spacing showed the highest number of siliques by plants and the highest productivity.
Keywords: Brassica napus L. var. oleifera; Preventive management; Brassica napus; antifungal agents